The White Octopus Hotel - Bell, Alex, 1986- (Del Rey, 2025)
"Journey to a magical hotel in the Swiss Alps, where two lost souls living in different centuries meet and discover if, behind the many doors, a second chance awaits"-- Provided by publisher.